AB1192 National barometer to assess the emotional aspects of patients with rheumatoid arthritis. opinar project. (15th June 2017) - Sanz, S Castañeda; Gonzalez-Gay, MA; Vicente, EF; Miguel, C Alegre de; Hera, M De la; Torrente-Segarra, V; Merino-Meléndez, L; Juan-Mas, A; Alcaide, L; Torralba, AI; Baquero, JL
Abstract : Background: The WHO defines health as the state of physical, psychic and social well-being. In contrast, patients with rheumatoid arthritis (RA) frequently report that treatment is directed mainly at combating physical affection and hardly anything to emotional and social aspects. Objectives: To assess the emotional impact and degree of satisfaction with the medical care received in the patient with poor prognosis RA. Methods: National, structured and anonymous survey of 26 questions conducted between March and July 2016. Responses were counted as percentages or as means/medians of the score given on a Likert scale from 1 to 10 (minimum and maximum, respectively). Analyzes were performed using Microsoft 2012: mean (m), standard deviation (SD), median (M), interquartile range (IQR) and statistical significance of differences (Student t test). The study was approved by the National Coordinator ConArtritis and the CEIC of the reference hospital. Results: The survey was completed by 100 of 122 enrollees, 75 by telephone and 25 via email; 83 women and 17 men, with a mean age of 49.4 years (SD 12.1); from all the Spanish Autonomous Communities. 52% were considered of poor prognosis (participant's own perception). 66.7% of self-perceived high-activity RA by patients exceeded the physician's impression; and 31.03% of the intermediate-activity. The degree of knowledge and the importance given to certain aspects of the disease in relation to the poor prognosis ranged from 8 to 9/10 in the different items analyzed. The awareness of their seropositivity against FR and ACPA was 77% and 17%, respectively. 63% consider the physical aspect more disabling, but 52% gave more value to feeling good emotionally. The mean treatment score for physical aspects was 7.07 (SD 2.52), whereas for emotional aspects was 3.39 (SD 2.57). 51.9% of self-considered poor prognosis patients believed that biological treatment was delayed and 50% related that to poorer outcome. 97% wanted to participate in the doctor's decisions, but 38% declared they had no choice. There were no statistically significant differences between the prognostic groups. Conclusions: More than half of the patients self-reported poor prognosis. Two-thirds estimated poorer health status than physicians if their RA was of high activity; 1/3 if it was intermediate. Patients considered all assessed aspects as determinants of poor prognosis (m>8). The degree of knowledge of their condition was high, being lower for joint damage and activity and prognostic markers. The beginning of treatment with biologicals was perceived as delayed in more than half of those who declared themselves with poor prognosis and half of them related it to a worse evolution. A high percentage of patients showed low satisfaction with the emotional attention received. Most claim to be more involved in medical decisions, although more than 1/3 does not seem to be able to do so. Acknowledgements: Coordinadora Nacional de Artritis (ConArtritis) Disclosure of Interest: None declared